Stages of development of leadership skills for dietitians (2014)
Based on a systematic literature review, scenarios for the development of leadership skills for Nutritionists-Dietitians are discussed, with the goal of presenting the main scenarios of leadership training, aimed at developing skills of professionals who face the challenge of leading teams to achieve high levels of performance in multiple contexts. Based on the evidence available, it is concluded the need for nutrition and dietetics professionals to develop leadership skills to positively influence the society and the environment in which they serve, and it is recommended to universities, organizations, guilds and associations to develop suitable leadership training programs with a focus on developing skills and competences to influence the environment.